2012
DOI: 10.6026/97320630008006
|View full text |Cite
|
Sign up to set email alerts
|

Accommodation of profound sequence differences at the interfaces of eubacterial RNA polymerase multi-protein assembly

Abstract: Evolutionarily divergent proteins have been shown to change their interacting partners. RNA polymerase assembly is one of the rare cases which retain its component proteins in the course of evolution. This ubiquitous molecular assembly, involved in transcription, consists of four core subunits (alpha, beta, betaprime, and omega), which assemble to form the core enzyme. Remarkably, the orientation of the four subunits in the complex is conserved from prokaryotes to eukaryotes although their sequence similarity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Our results indicate that it is the interaction between α-subunit of the RNAP and the UP-like elements that is affected by the T-tract length, through change in DNA structure. Homology predictions has shown that the RNAP α- and ω-subunits are more divergent between different bacterial species than the remaining subunits [75] and thus, interaction of RNAP to DNA structures or DNA binding trans-acting factors might deviate from E. coli . Borin et al showed that the linker region between the αCTD and αNTD is longer in H. pylori compared to the E. coli α-subunit.…”
Section: Resultsmentioning
confidence: 99%
“…Our results indicate that it is the interaction between α-subunit of the RNAP and the UP-like elements that is affected by the T-tract length, through change in DNA structure. Homology predictions has shown that the RNAP α- and ω-subunits are more divergent between different bacterial species than the remaining subunits [75] and thus, interaction of RNAP to DNA structures or DNA binding trans-acting factors might deviate from E. coli . Borin et al showed that the linker region between the αCTD and αNTD is longer in H. pylori compared to the E. coli α-subunit.…”
Section: Resultsmentioning
confidence: 99%